PENDAMPINGAN APLIKASI MENDENGAR MUSIK DALAM MENURUNANKAN TEKANAN DARAH PADA LANSIA - Zakiyah Yasin; Mujib Hannan, Nelyta Oktavianisya, Emdat Suprayitno (Adiba Aisha Amira, 2022)
High blood pressure cases develop with age, and most deaths are caused by hypertension. This can cause problems in the lives of the elderly and will affect their quality of life. The situation in Talango Village, Talango District, Sumenep Regency is the lack of public knowledge about non-pharmacological treatments for lowering blood pressure. The solution to this problem is to assist with the Classical Music Listening Application to Lower Blood Pressure in the Elderly in Talango Village, Talango District, Sumenep Regency. The method in this PKM is socialization to increase community knowledge in Talango Village. The results of this mentoring activity had a good impact, namely that at this time, there were (83.3%) of the elderly and their blood pressure decreased.